Single event phenomena / George C. Messenger, Milton S. Ash - Ash, Milton S. (Chapman & Hall, 1997)
Electronic designers including those involved in spacecraft, missle, and aircraft avionics and ground systems will welcome a comprehensive treatment of SEU. This book will be used to achieve hardened designs necessary to mitigate the effects of SEU. Since SEU is a growing problem as future chip transitor densities are ever-increasing, this volume will be an invaluable reference for any one working in this area.